Association of Simian Virus 40 T Antigen with Simian Virus 40 Nucleoprotein Complexes - Mann, Kristine (1979)
Viral nucleoprotein complexes were extracted from the nuclei of simian virus 40 (SV40)-infected TC7 cells by low-salt treatment in the absence of detergent, followed by sedimentation on neutral sucrose gradients. Two forms of SV40 nucleoprotein complexes, those containing SV40 replicative intermediate DNA and those containing SV40 (I) DNA, were separated from one another and were found to have sedimentation values of 125 and 93S, respectively. [(35)S]methioninelabeled proteins in the nucleoprotein complexes were analyzed by sodium dodecyl sulfate-polyacrylamide gel electrophoresis. In addition to VP1, VP3, and histones, a protein with a molecular weight of 100,000 (100K) is present in the nucleoprotein complexes containing SV40 (I) DNA. The 100K protein was confirmed as SV40 100K T antigen, both by immunoprecipitation with SV40 anti-T serum and by tryptic peptide mapping. The 100K T antigen is predominantly associated with the SV40 (I) DNA-containing complexes. The 17K T antigen, however, is not associated with the SV40 (I) DNA-containing nucleoprotein complexes. The functional significance of the SV40 100K T antigen in the SV40 (I) DNA-containing nucleoprotein complexes was examined by immunoprecipitation of complexes from tsA58-infected TC7 cells. The 100K T antigen is present in nucleoprotein complexes extracted from cells grown at the permissive temperature but is clearly absent from complexes extracted from cells grown at the permissive temperature and shifted up to the nonpermissive temperature for 1 h before extraction, suggesting that the association of the 100K T antigen with the SV40 nucleoprotein complexes is involved in the initiation of SV40 DNA synthesis.